Connection of quasifiniteness and regularity properties in problems of semi-infinite linear programming - Astafiev , N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We generalize the approach, introduced by S. N. Chernikov, that reduces nonhomogeneous systems to homogeneous ones, and apply this approach, in particular, in a study of a class of finitary-definite problems. The generalization consists of such a modification as the approach for a more general class of problems, namely quasi-finitary problems, including the irregular case.